2000
DOI: 10.1029/2000gc000108
|View full text |Cite
|
Sign up to set email alerts
|

Vailulu'u undersea volcano: The New Samoa

Abstract: [1] Abstract: Vailulu'u Seamount is identified as an active volcano marking the current location of the Samoan hotspot. This seamount is located 45 km east of Ta'u Island, Samoa, at 169803.5 0 W, 14812.9 0 S. Vailulu'u defines the easternmost edge of the Samoan Swell, rising from the 5000-m ocean floor to a summit depth of 590 m and marked by a 400-m-deep and 2-km-wide summit crater. Its broad western rift and stellate morphology brand it as a juvenile progeny of Ta'u. Seven dredges, ranging from the summit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 32 publications
3
81
0
Order By: Relevance
“…1); it rises from a 5000 m deep seafloor to a summit depth of 590 m and rests 45 km east of its nearest neighbor, Ta'u Island (Hart et al, 2000). Vailulu'u has been shown to be both volcanically and hydrothermally very active (Hart et al, 2000;Hart et al, 2003;Staudigel et al, 2004;Konter et al, 2004).…”
Section: Geological and Geochemical Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…1); it rises from a 5000 m deep seafloor to a summit depth of 590 m and rests 45 km east of its nearest neighbor, Ta'u Island (Hart et al, 2000). Vailulu'u has been shown to be both volcanically and hydrothermally very active (Hart et al, 2000;Hart et al, 2003;Staudigel et al, 2004;Konter et al, 2004).…”
Section: Geological and Geochemical Settingmentioning
confidence: 99%
“…1); it rises from a 5000 m deep seafloor to a summit depth of 590 m and rests 45 km east of its nearest neighbor, Ta'u Island (Hart et al, 2000). Vailulu'u has been shown to be both volcanically and hydrothermally very active (Hart et al, 2000;Hart et al, 2003;Staudigel et al, 2004;Konter et al, 2004). The power output from Vailuluu's summit crater is estimated to be 610-760 MW, the equivalent of 20-100 Mid-Ocean Ridge black smokers; Mn export is estimated at 240-300 kg/day, or the equivalent of about 10 black smokers Hart et al, 2003).…”
Section: Geological and Geochemical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Three previous expeditions in 1999-2001 showed that Vailulu'u volcano is seismically and hydrothermally active, with an average of four local earthquakes per day and hydrothermal fluxes that rival those of black smokers at midocean ridges (11)(12)(13)(14). The return to Vailulu'u in 2005 revealed a new, 300-m-high volcanic cone that had grown in the crater of Vailulu'u from 1,000-m water depth and that forms a new central summit, named Nafanua.…”
Section: Resultsmentioning
confidence: 99%
“…1). Crater waters are expelled through all breaches during ''low tides,'' as the hydrothermal dome collapses and exhales, forming a ''smokering'' around the summit of Vailulu'u (11).…”
Section: Vent Complex IImentioning
confidence: 99%